2007
DOI: 10.1029/2007gl032324
|View full text |Cite
|
Sign up to set email alerts
|

Urban heat island in the subsurface

Abstract: The urban heat island effect has received significant attention in recent years due to the possible effect on long‐term meteorological records. Recent studies of this phenomenon have suggested that this may not be important to estimates of regional climate change once data are properly corrected. However, surface air temperatures within urban environments have significant variation, making correction difficult. In the current study, we examine subsurface temperatures in an urban environment and the surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
85
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(98 citation statements)
references
References 26 publications
12
85
0
1
Order By: Relevance
“…Other site maintenance related issues (sensor degradation, debris, mowing) may have contributed to data trend inconsistencies. Despite vegetation (crop types) and management related cover differences (assumed a negligible effect over long-term), soil temperature data showed a gradient (5 cm depth: 14.75 and 14.07 °C for Sanborn and South Farm, respectively; 10 cm depth: 14.63 and 14.25 °C for Sanborn and South Farm, respectively) between rural and urban temperatures which was correlated with the air temperature gradient (13.47 and 12.89 °C of Sanborn and South Farm, respectively), and similarly equivalent attenuation of surface heating with increasing depth, consistent with results of previous studies [20,22,30,32]. Ferguson and Woodbury emphasized in 2007 that temperature effects of UHI at the surface are positively correlated with temperature effects of UHI at the subsurface [21].…”
Section: Long-term Climate Trendssupporting
confidence: 80%
See 1 more Smart Citation
“…Other site maintenance related issues (sensor degradation, debris, mowing) may have contributed to data trend inconsistencies. Despite vegetation (crop types) and management related cover differences (assumed a negligible effect over long-term), soil temperature data showed a gradient (5 cm depth: 14.75 and 14.07 °C for Sanborn and South Farm, respectively; 10 cm depth: 14.63 and 14.25 °C for Sanborn and South Farm, respectively) between rural and urban temperatures which was correlated with the air temperature gradient (13.47 and 12.89 °C of Sanborn and South Farm, respectively), and similarly equivalent attenuation of surface heating with increasing depth, consistent with results of previous studies [20,22,30,32]. Ferguson and Woodbury emphasized in 2007 that temperature effects of UHI at the surface are positively correlated with temperature effects of UHI at the subsurface [21].…”
Section: Long-term Climate Trendssupporting
confidence: 80%
“…Urban areas with elevated air temperatures resulting from UHI exhibit higher subsurface temperatures than rural areas [21]. The increase in subsurface temperature is a result of conduction of surface heat, and the effects may continue downward for several meters into the soil [22]. The extent and depth of soil heating is highly dependent on soil thermal properties, which are influenced by soil structure and texture and are therefore often highly variable between sites [21].…”
Section: Alterations To Climate Variablesmentioning
confidence: 99%
“…The maximum T 2 changes are usually found in the city centers of the PRD region, with typical increments of over 1.1 • in January and of over 0.5 • in July. These findings are comparable to the values estimated for other cities (Fan and Sailor, 2005;Ferguson and Woodbury, 2007;Zhu et al, 2010;Menberg et al, 2013;Wu and Yang, 2013;Bohnenstengel et al, 2014;Yu et al, 2014;Xie et al, 2016) and can be confirmed by similar research in South China (Meng et al, 2011;Feng et al, 2012Feng et al, , 2014. Figure 4e and f present the vertical changes in air temperature from the surface to the 800 hPa layer along the line AB (shown in Fig.…”
Section: Changes In Surface Energy and Air Temperaturesupporting
confidence: 79%
“…Sometimes, the fluxes might exceed the value of 100 W m −2 (Iamarino et al, 2012;Quah and Roth, 2012;Lu et al, 2016;Xie et al, 2016), with the extreme value of 1590 W m −2 in the densest part of Tokyo at the peak of air-conditioning demand (Ichinose et al, 1999). With regard to their effects, the researchers found that AH fluxes can cause urban air temperatures to increase by several degrees (Fan and Sailor, 2005;Ferguson and Woodbury, 2007;Zhu et al, 2010;Feng et al, 2012Feng et al, , 2014Menberg et al, 2013;Wu and Yang, 2013;Bohnenstengel et al, 2014;Chen et al, , 2014aYu et al, 2014;Xie et al, 2016), induce the atmosphere to be more turbulent and unstable, change the urban heat island circulation, strengthen vertical air movement (Ichinose et al, 1999;Block et al, 2004;Fan and Sailor, 2005;Feng et al, 2012Feng et al, , 2014Bohnenstengel et al, 2014;Yu et al, 2014;Xie et al, 2016), enhance the convergence of water vapor in cities, and change the regional precipitation patterns (Feng et al, 2012(Feng et al, , 2014Xie et al, 2016). In spite of meteorology conditions and air quality being inextricably linked, however, few investigations have paid attention to how the air quality is altered by the changes in regional meteorology induced by anthropogenic heat.…”
mentioning
confidence: 99%
See 1 more Smart Citation